Inhibition Effects of Nitrones on the Corrosion of Mild Steel in Organic Acid Media - Thirumalaikumar,M. (2011)
Aromatic nitrones have been synthesized and investigated for their function as inhibitor for the corrosion of mild steel in the organic acid media - 20% formic acid and 20% acetic acid at various inhibitor concentrations in the range of 50 - 150 ppm. Weight loss measurements and potentio-dynamic polarization studies reveal that the nitrones behave as mixed type inhibitors. Among the nitrones tested, para-methyl substituted derivatives perform better as inhibitors than the un-substituted nitrones.